Metabólitos especiais das folhas de Zanthoxylum riedelianum Engl. e da casca do caule de Zanthoxylum rigidum Humb. Bonpl. ex Willd (RUTACEAE) - Beirigo, Pâmela Jordana dos Santos (2013)
The family Rutaceae has about 150 genera and 2000 species, which are distributed in the tropics, subtropics and temperate regions of the southern hemisphere. In Brazil is represented by about 32 genera and 150 species. This family is characterized by producing a variety of metabolites, many of great pharmacological interest. The genus Zanthoxylum is belonging to the family Rutaceae, many species of this genus are used in folk medicine against inflammatory disorders or infections. In the more than 200 species belonging to this genus are described occurrence of coumarins, lignans, flavonoids, alkaloids, essential oils and unsaturated alkylamides. This paper describes the phytochemical study of two species of this genus: Zanthoxylum rigidum and Zanthoxylum riedelianum. The phytochemical study involved from the preparation of extracts, followed by fractionation and isolation of compounds using different chromatographic methods. The spectroscopic analysis allowed the identification of substances known and characterization unpublished. Chromatographic fractionation of the stem bark of Zanthoxylum rigidum led to the isolation and identification substance N-trans-cafeoiltiramina and acid-3-β-hydroxy-12-us-on-28-oic acid. Leaves isolated Zanthoxylum riedelianum substance 3,4-dihydroxy methyl cinnamate, protocatechuic acid, benzoilfenilalanilato N-N-benzoilfenilalanina and a new octapeptide which was named ciclozanthoxylano B.